Individual features in vocalization of the Mashona mole-rat (Fukomys darlingi) - Dvořáková, Veronika (Jihočeská univerzita, 2014)
The significance of vocal communication in subterranean rodents was confirmed. In this study I tested whether vocalization of the Mashona mole-rats (Fukomys darlingi) differs individually and what information about signaller are these mole-rats able to obtain using only acoustic cues.
Individual features in vocalization of the Mashona mole-rat (Fukomys darlingi)
Keywords: Mashona mole-rat; Fukomys darlingi; vocalization; individuality; Mashona mole-rat; Fukomys darlingi; vocalization; individuality